2019
DOI: 10.1177/0300060519887275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of erlotinib as neoadjuvant regimen in EGFR-mutant locally advanced non-small cell lung cancer patients

Abstract: Background The optimal neoadjuvant regimen for locally advanced resectable non-small cell lung cancer (NSCLC) remains controversial. EGFR inhibitors have significantly improved survival in patients with EGFR-mutant advanced NSCLC. However, their efficacy in neoadjuvant settings, particularly for treating locally advanced NSCLC, remains unclear. We compared the clinical benefits of chemotherapy and erlotinib as neoadjuvant therapy for stage IIIA NSCLC. Method Thirty-one treatment-naïve Chinese patients with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…For the comparison of the survival outcomes of neoadjuvant EGFR-TKIs versus neoadjuvant chemotherapy, Zhong et al (11) reported that the median progression-free survival (PFS) and OS were significantly longer with erlotinib than with gemcitabine plus cisplatin chemotherapy (HR, 0.39; 95% CI, 0.23 to 0.67; P < 0.001; and HR, 0.77; 95% CI, 0.41 to 1.45; P = 0.417). Similar to these results, in one excluded study, Xiong et al (12) reported that erlotinib may have a survival benefit compared with cisplatin-based doublet chemotherapy in terms of DFS (HR, 0.51; 95% CI, 0.13 to 2.01; P =0.39) and OS (HR, 0.45; 95% CI, 0.04 to 5.54; P =0.12), but a significant difference was not found. However, the chemotherapy arm in this study included vinorelbine, gemcitabine, paclitaxel, docetaxel or pemetrexed with limited participants (n=16).…”
Section: The Impact Of Neoadjuvant Egfr-tkis On Survivalsupporting
confidence: 73%
See 1 more Smart Citation
“…For the comparison of the survival outcomes of neoadjuvant EGFR-TKIs versus neoadjuvant chemotherapy, Zhong et al (11) reported that the median progression-free survival (PFS) and OS were significantly longer with erlotinib than with gemcitabine plus cisplatin chemotherapy (HR, 0.39; 95% CI, 0.23 to 0.67; P < 0.001; and HR, 0.77; 95% CI, 0.41 to 1.45; P = 0.417). Similar to these results, in one excluded study, Xiong et al (12) reported that erlotinib may have a survival benefit compared with cisplatin-based doublet chemotherapy in terms of DFS (HR, 0.51; 95% CI, 0.13 to 2.01; P =0.39) and OS (HR, 0.45; 95% CI, 0.04 to 5.54; P =0.12), but a significant difference was not found. However, the chemotherapy arm in this study included vinorelbine, gemcitabine, paclitaxel, docetaxel or pemetrexed with limited participants (n=16).…”
Section: The Impact Of Neoadjuvant Egfr-tkis On Survivalsupporting
confidence: 73%
“…Since 2016, the study designs have tended to focus on NSCLC patients with stage II and stage III disease (8,9) with EGFR-sensitive mutations. In addition, a comparison of neoadjuvant EGFR-TKIs and chemotherapy (11,12) suggests that neoadjuvant EGFR-TKIs can improve patient prognosis compared with chemotherapy. Nevertheless, the chemotherapy group in the study by Zhong et al (11) was administered gemcitabine plus cisplatin, while in the study by Xiong et al (12), cisplatin-based doublet chemotherapies including vinorelbine, gemcitabine, paclitaxel, docetaxel or pemetrexed were administered.…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, 50% of patients achieved a PR, and the remaining patients achieved stable disease (SD). The median diseasefree survival (DFS) of patients who underwent surgery was 10.3 months; among the 19 patients who received neoadjuvant therapy, the progression-free survival (PFS) and the median overall survival (OS) were 11.2 and 51.6 months, respectively (1). The NCT01833572 study is a prospective single-arm phase II clinical study to evaluate the efficacy of gefitinib as a neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…On a pathological level, 50% of patients had a partial response, while 50% had stable disease [ 26 ]. The third study compared neoadjuvant erlotinib among 15 patients whose tumors had EGFR mutations to chemotherapy in 16 patients without these alterations [ 27 ]. The authors report a trend towards better response rate, pathological response rates, and overall survival.…”
Section: Epidermal Growth Factor Receptor (Egfr) Mutationsmentioning
confidence: 99%